Preliminary results of abundance determination of IRAS 09276+4454 - Klochkova, V. G.; Mishenina, T. V.; Panchuk, V. E. (Одеські астрономічні публікації, 2017)
The model atmosphere parameters and chemical abundance curve are derived for the infrared source IRAS O9276-I-4454 identified with the peculiare supergiant HD 82040 (Мб). The effective temperature from hand head intensity relations of TiO oz system was determined. The abundances of 11 chemical elements in atmosphere of IRAS O9276-I-4454 were estimated. The chemical abundance pattern is close to the solar one.